Suggesting guidelines for public pension funds governance - Bebczuk, Ricardo Néstor (2011)
Driven by the financial distress of many social security systems worldwide, national public pension funds (PPFs) have proliferated in recent years. Considering the fact that in 2007, they managed assets globally by more than four trillion and a half dollars, oversight of these pension schemes is utterly warranted. Since PPFs are ultimately financial intermediaries, strict regulation and close scrutiny of their stakeholders is desirable in order to avoid potential conflicts of interest between the owners and the managers of the funds, which are exacerbated in the case of pension funds administered by the public sector because of many reasons discussed in the paper. Governance standards should be equally rigorous as those applicable to private pension funds. Additionally, sound institutional structure is needed to keep under control undue political interference by promoting good practices of disclosure and accountability. According to several case studies, at present, national PPFs display heterogeneous standards in this regard. In light of their size and intrinsic governance shortcomings, there exists a pressing need for Guidelines of Good Practices for Public Pension Funds Governance that lays the grounds on which these particular institutional investors should be run to achieve their stated purposes. The current document provides Guidelines proposing as key areas of a PPF the maximization of the risk-adjusted net return on the reserves, collections of contributions, payments of benefits, compliance enforcement, and account management. In turn, an environment conducive to the accomplishment of these objectives must be grounded on three pillars: (i) Internal Governance Structure: a good internal governance structure is one that ensures that the Fund will be administered by a committed and professional governing body where decisions are made after careful deliberation and agreement between its members in accordance to the Fund’s objectives and fully consistent with the long-term commitments made to plan members; (ii) Investment Policy: a good investment policy is one that clearly and explicitly sets forth in advance the short- and long-term asset allocation, its rationale in light of the Fund’s goal, the risks involved, and the tools to be used to deal with deviations from such goal; and (iii) Transparency and Accountability: it is crucial that relevant and timely information be disclosed to all stakeholders so as to facilitate monitoring and oversight of Fund authorities and actions be taken to detect and punish opportunistic behaviors and bad performance. After listing the principles recommended for a good framework of governance, accountability and transparency, the document develops a Manual that complements the Guidelines with its technical rationale, some operational aspects and international experience as applicable.